Analisis Implementasi Pendidikan Moral Pancasila Sebagai Upaya Pencegahan Bulliying di Sekolah - Eri Susanto (Cendikia: Jurnal Pendidikan dan Pengajaran, 2023)
This research aims to analyse the implementation of Pancasila moral education as an effort to prevent bullying in schools. This research uses a qualitative methodology, combining an extensive literature review from various sources, including traditional print media and electronic sources such as books and online journals. I did a search using Google Scholar to find scientific articles relevant to the topics "Pancasila Moral Learning" and "Bullying". Scientists collect various articles from search results. Next, individuals were selected who met the specified criteria, especially those involved in discussions regarding Pancasila moral education and bullying. The methodology used in this research uses documentation procedures that combine various sources, including treatises, literature, essays, scientific works, journals, and newspapers. From the results and analysis of Pancasila moral education data, we can help foster a school environment that prioritises friendliness and eliminates violence, which ultimately prevents bullying.